2012
DOI: 10.1016/j.jim.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of factors influencing on-chip complement activation to optimize parallel measurement of antibody and complement proteins on antigen microarrays

Abstract: Abstract:Binding of immunoglobulins and complement fragments to targets of adaptive immune responses can be monitored using collections of arrayed antigens and are used to generate profiles of antibody binding and function. The collection of reliable data on these reactions on a large scale requires the establishment of criteria from sample collection through reaction conditions to normalization strategies. We characterized the detection of IgG, complement C3 and C4 under conditions that closely imitate in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
6
0
1
Order By: Relevance
“…A large number of inhibitors have been applied to block complement activation or reduce its consumption [10][11][12]. However, studies that evaluated the role of exogenous complement protein in sepsis have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of inhibitors have been applied to block complement activation or reduce its consumption [10][11][12]. However, studies that evaluated the role of exogenous complement protein in sepsis have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Harboe et al reported that hemolytic activity of the serum is lost at 1∶16 dilution for assaying the alternative pathway and at 1∶1024 dilution for assaying the classical pathway [38]. We have previously shown that 1∶5–1∶10 serum dilutions give the highest signal-to-noise ratios for complement measurement on nitrocellulose-coated protein microarray slides [39]. Trouw et al also used a serum dilution of 1∶10 in their ELISA based ACPA induced complement activation measurements [36].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was more pronounced regarding the detection of IgG than IgM ( Figure 3 ) . To circumvent this effect, either higher serum dilutions can be utilized [39] or the assay buffer can be supplemented with EDTA, which blocks the complement activation. Here we used the latter approach since our aim was to measure antibody levels under assay conditions as identical as possible to the conditions used for measurement of complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that parallel detection of immunoglobulins and complement proteins has certain technical tricks, which were recently described [9].…”
Section: Interpreting Complement Activation As a Function Of Antibodymentioning
confidence: 99%
“…Serum concentrations of complement C3 and C4 vary in the range of 1.0-1.85 g/l and 0.2-0.45 g/l, respectively; in a similar manner, normal complement activity, as assessed by CH50 measurement, also spans a log 2 range. Our approach is to determine the relative complement activating properties of antigen-bound antibodies, therefore we normalize results to complement deposition on obligate complement activating substances [9]. This approach allowed the distinction between antibody profiles induced by different adjuvants [13] and to monitor the progressive qualitative change of antinuclear antibodies in a murine model of lupus erythematosus [14].…”
Section: D Profiles -Comparing Serum Samplesmentioning
confidence: 99%